EXONERATION CLAUSE PADA PERJANJIAN STANDAR PEMBIAYAAN KONSUMEN - Dewi, Putu Eka Trisna (Fakultas Hukum Universitas Mahasaraswati Denpasar, 2016)
In general, the business activities can not be separated from an agreement to ensure legal certainty. Testament as we know it is an event where one can promise to someone other or where two or more mutually pledged to carry out a thing. Currently, there is a wide range of agreement or contract is a form of derivative agreements of the agreements already provided for in the Civil Law Act (Civil Code) as a result of the principle of freedom of contract. The subject of the agreement was not only a person but also the body, whether incorporated or unincorporated. One of the agreements arising from the development of the business world is a consumer financing agreement in which the shape of the agreement in the form of raw agreement. Because of its raw argued that the treaty does not reflect a sense of fairness and detrimental to one of the parties which are in the field of contract law known as the exoneration clause.